Characteristics and risk factors of candidemia in pediatric intensive care unit of a tertiary care children's hospital in Egypt - Moustafa Hegazi; Alaa Abdelkader; Maysaa Zaki; Basem El-Deek (Journal of Infection in Developing Countries)
Introduction: This study was conducted to determine characteristics of Candida colonization and candidemia in the pediatric intensive care unit (PICU) of a tertiary care children's hospital. Methodology: Patients between 6 months and 15 years of age consecutively admitted to the PICU of Mansoura University Children’s Hospital in Mansoura, Egypt, during one year period, were evaluated for Candida colonization and candidemia. Susceptibility of Candida species isolated from blood to fluconazole and amphotericin B was determined by Etest. Results: Sixty-six patients without prior fluconazole prophylaxis had 88 episodes of candidemia, representing 19% of all cases with blood stream infections (BSIs).  Candida albicans (CA) and non-albicans Candida (NAC) species accounted for 40% and 60% of candidemia episodes respectively. C. parapsilosis, C. tropicalis, and C. glabrata accounted for 25%, 17%, and 8% of NAC candidemias respectively. Fluconazole resistance was detected in 11.4% and 18.9% of CA and NAC isolates respectively. Of the fluconazole resistant NAC isolates, four were C. krusei. Amphotericin B resistance was detected in 17% of NAC isolates. Candida colonization was detected in 78.8% of patients. Compared to CA candidemia, higher risk for NAC candidemia was associated with age older than 1 year, Candida isolation from endotracheal tube (ETT) and from central venous catheter. Mortality rate was 42.4%, attributable mortality of candidemia was 16.7%. Regression analysis showed that the most significant independent predictors of death were ETT and mechanical ventilation (MV), MV longer than 7 days, and candiduria. Conclusions: This study presents important epidemiological features of Candida BSIs in a non-neonatal population.